MANAJEMEN PENDISTRIBUSIAN DANA ZAKAT PROFESI DI BAZNAS KABUPATEN PEMALANG - Uswatun Niswah (Jurnal Manajemen Dakwah, 2023)
This study aims to find out how the management of the distribution of professional zakat funds at the National Amil Zakat Agency (BAZNAS) in Pemalang Regency. This is interesting to study because professional zakat occupies the first position in obtaining the most funds, although in practice, there are still government employees (ASN) who are late in paying zakat. The results of this study indicate that the management of the distribution of professional zakat funds at BAZNAS Pemalang Regency has implemented management functions such as planning, organizing, actuating, and also supervising. In its implementation, the supporting factors for the distribution of professional zakat funds at BAZNAS Kab. Pemalang is the support from the government and the community, the strategic location of the BAZNAS office, as well as the availability of UPZ in each agency which affects the acquisition of funds and their distribution. Meanwhile, the inhibiting factor for the distribution of zakat funds at BAZNAS Kab. In Pemalang, there are still many civil servants who are late paying zakat, lack of human resources in distribution activities, and the attitude of mustahik who are less able to use aid funds effectively. This research is a descriptive qualitative research. Data collection techniques were carried out through observation, interviews, and documentation. Meanwhile, in the analysis, it uses the model from Matwe G. Miles and Michael Huberman with the steps of analysis including data reduction, data display, and conclusion/verifying.Keywords: Management, Zakat Distribution, Professional Zakat, BAZNAS Pemalang Regency